2017
DOI: 10.1021/acs.nanolett.7b01593
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Surface Curvature Effects on Ligand–Nanoparticle Interactions: A Plasmon-Enhanced Spectroscopic Study of Thiolated Ligand Adsorption, Desorption, and Exchange on Gold Nanoparticles

Abstract: The interfacial adsorption, desorption, and exchange behaviors of thiolated ligands on nanotextured Au nanoparticle surfaces exhibit phenomenal site-to-site variations essentially dictated by the local surface curvatures, resulting in heterogeneous thermodynamic and kinetic profiles remarkably more sophisticated than those associated with the self-assembly of organothiol ligand monolayers on atomically flat Au surfaces. Here we use plasmon-enhanced Raman scattering as a spectroscopic tool combining time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 73 publications
4
86
1
Order By: Relevance
“…Very recently, it has been reported that single gold atom positional change in the plasmonic molecular junctions of the NPoM configuration can lead to the transient formation of a “picocavity,” which leads to a high SERS enhancement and makes single molecule changes observable in the SERS trajectories . Nanoscale surface curvature also plays important roles to promote such variations . Therefore, it is reasonable that single molecule fluctuations can be observed in these highly dynamic GNP/molecule/GNE junctions involving tens to hundreds molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, it has been reported that single gold atom positional change in the plasmonic molecular junctions of the NPoM configuration can lead to the transient formation of a “picocavity,” which leads to a high SERS enhancement and makes single molecule changes observable in the SERS trajectories . Nanoscale surface curvature also plays important roles to promote such variations . Therefore, it is reasonable that single molecule fluctuations can be observed in these highly dynamic GNP/molecule/GNE junctions involving tens to hundreds molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[43] Nanoscale surface curvature also plays important roles to promote such variations. [44] Therefore, it is reasonable that single molecule fluctuations can be observed in these highly dynamic GNP/molecule/GNE junctions involving tens to hundreds molecules.…”
Section: Sers Spectral Changes Inmentioning
confidence: 99%
“…Vertegel et al (2004) observed a greater loss of lysozyme conformation adsorbed onto larger silica nanoparticles under otherwise similar conditions. About the gold nanoparticles, the effects of curvature on ligand interaction remains a complicate issue (Villarreal et al, 2017). Villarreal et al (2017) CD spectroscopy method is commonly used to determine protein structure and its interaction with other molecules.…”
Section: Physicochemical Characterization Of Gold Nanoparticles Decormentioning
confidence: 99%
“…About the gold nanoparticles, the effects of curvature on ligand interaction remains a complicate issue (Villarreal et al, 2017). Villarreal et al (2017) CD spectroscopy method is commonly used to determine protein structure and its interaction with other molecules. CD spectroscopy confirmed the Trastuzumab conjugation to the gold nanoparticles (Figure 3D and Supplementary Figure S4), but also suggested a correlation between Trastuzumab-conjugated secondary structure maintenance and the particle hydrodynamic radius (R).…”
Section: Physicochemical Characterization Of Gold Nanoparticles Decormentioning
confidence: 99%
“…This defies the idea that local NP curvature is responsible for the shift in oxidation potential. 38 We show that the oxidation potential is actually more related to the total surface area-to-volume ratio (SA/V). These results also explain why previous papers did not observe a shift in oxidation potential for NPs below 40 nm.…”
Section: Aggregation Of Metal Npsmentioning
confidence: 81%